The Role of Leadership and Communication Competence in Increasing Learning Motivation in the Kampus Mengajar Program - Malik, Abdul; Putri, Liza Diniarizky; Utomo, Wisnu Prasetya (Universitas Gadjah Mada, 2024)
Introduction/Main Objectives: Kampus Mengajar (Teaching Campus) is a program that provides opportunities for university students to learn outside the classroom for 1 (one) semester by becoming teaching partners to make innovation in the development of creative and innovative learning models and strategies in targeted education units. This program focuses on increasing school students' literacy and numeracy skills in targeted schools. Background Problems: This research tries to elaborate further on how university students play a role in efforts to increase students' learning motivation in the target schools. Novelty: The research that examined leadership and communication competencies associated with increasing students' learning motivation has never been described in the Kampus Mengajar Program evaluation. Research Methods: Qualitative approach is used to collect the data. The data used in this study were primary and secondary. Primary data was obtained from non-participant observations, interviews, and focus group discussions with students and teachers. Secondary data were obtained from students' report documents and other relevant literature. Finding/Results: Based on the results of the research, it was found that participants' leadership and communication competencies play an essential role in increasing students' learning motivation, which has a positive effect on increasing their literacy and numeracy skills. Conclusion: it could be concluded that university students, as the program participants were able to build their leadership attitudes successfully.